2011
DOI: 10.2174/1874450801105010047
|View full text |Cite
|
Sign up to set email alerts
|

Digestive Enzymes in Larvae and Juveniles of Farmed Sharpsnout Seabream (Diplodus puntazzo) (Cetti, 1777)

Abstract: Abstract:The ontogenetic development and pattern of main digestive enzyme activities (proteases, carbohydrases and lipases) were investigated in farmed sharpsnout seabream Diplodus puntazzo larvae and juveniles, during the passage from the larval stage to adult (from 21 to 277 days after hatching -DAH). Larvae showed exponential growth, thus confirming that Rotifers and Artemia nauplii are suitable preys for early feeding of D. puntazzo larvae.Pepsin activity was low in the larvae, but it increased afterwards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 80 publications
3
6
1
4
Order By: Relevance
“…In this study, the highest amylase activity was found at pH 6.9 and 8.1, but it decreased at pH 10.0. The results of this study are lower than in previous studies on fish Betta splendens and Diplodus puntazzo (Savona et al, 2011). High amylase activity at neutral to slightly alkaline pH, which reflects that the starch hydrolysis process occurs at a neutral to alkaline condition.…”
Section: Resultscontrasting
confidence: 92%
See 4 more Smart Citations
“…In this study, the highest amylase activity was found at pH 6.9 and 8.1, but it decreased at pH 10.0. The results of this study are lower than in previous studies on fish Betta splendens and Diplodus puntazzo (Savona et al, 2011). High amylase activity at neutral to slightly alkaline pH, which reflects that the starch hydrolysis process occurs at a neutral to alkaline condition.…”
Section: Resultscontrasting
confidence: 92%
“…The activities of cellulose in the intestine of fish were also shown in previous studies on fish omnivore (Fagbenro et al, 2005;Tongsiri, Mang-Amphan & Peerapornpisal, 2010;Savona et al, 2011). However, previous studies showed that cellulose activity was related to the composition of the feed in the digestive tract.…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations